Technology Entrepreneurship Intention among Higher Education Institutions Students: A Literature Review - Lina Nadia Abd Rahim; Nur Atiqah Zakiyyah Ramlee; Ehsan Fansuree Mohd Surin; Hardy Loh Rahim (Information Management and Business Review, 2023)
Technology entrepreneurship is a new breed of entrepreneurship in a technology context, where it merges technology prowess and entrepreneurial skills. The intention to become technopreneurs among students from higher education institutions has become more and more prominent since it can be seen as a valuable way to contribute to the labor market to solve unemployment issues. However, despite data showing that the unemployment rate in Malaysia post-COVID is at a worrying state, studies on technology entrepreneurship intention are still lacking, with few areas being under-researched. This paper attempts to provide a review of existing academic literature on technology entrepreneurship intention among university students, revealing the current state and future direction of technology entrepreneurship intention research. Using a systematic literature review (SLR) method, the research papers were analyzed between the years 2017 and 2023 (7 years) to see the trend in the current years. The result shows that previous studies do not cover the subject comprehensively. Subjective norms were the least studied factor, despite their importance in shaping an individual’s behavior and intention. It was also found that none of the papers studied the role of government support and social media towards technology entrepreneurship intention. The identification of these under-researched areas will provide future directions for researchers to empirically study the factors. This paper may also provide future directions for the government in ensuring that more graduates have the intention to pursue technology entrepreneurship which will in turn contribute to the country’s economic growth.